Climate change litigation : regulatory pathways to cleaner energy - Peel, Jacqueline; Osofsky, Hari M., 1972- (Cambridge, United Kingdom : Cambridge University Press, 2015)
'This examination of the role of litigation in addressing the problem of climate change focuses not only on how the massive and growing number of lawsuits influences regulation directly but also on how the lawsuits shape corporate behavior and public opinion. It provides readers with an understanding of how these lawsuits have shaped approaches to mitigation and adaptation and have been used to try to force and to block regulation. There is a particular emphasis on lawsuits in the United States and Australia, the two jurisdictions that have had the most climate change litigation in the world, and the lessons supply broader insights into the role of courts in addressing climate change'--
Machine generated contents note: 1. Why climate change litigation matters; 2. Model for understanding litigation's regulatory impact; 3. Litigation as a mitigation tool; 4. Litigation as an adaptation tool; 5. Corporate responses to litigation; 6. Litigation's role in shaping social norms; 7. Barriers to progress through litigation; 8. The future of climate change litigation.
Includes bibliographical references and index.
Keywords: Climatic changes -- Law and legislation -- Australia; Climatic changes -- Law and legislation -- United States; Actions and defenses -- Australia; Actions and defenses -- United States; Liability for environmental damages -- Australia; Liability for environmental damages -- United States